Visiting Albert Watkins in Huntington Beach - Watkins, Howard::::::::: (1986)
Front: Robin Watkins and Adam Watkins; Back: Howard Watkins, Christine Watkins, Albert Watkins and Rose O'Reilly in front of 207 Geneva Avenue Ham radio tower in backyard